A Possibility of Pulsed Power Increasingof X-Band Relativistic Backward Wave Oscillator; 15th Symposium on High Current Electronics, September 21-26, 2008 - Totmeninov E. M. Evgeny Markovich; Klimov A. I. Aleksey Ivanovich; Kurkan I. K. Ivan Konstantinovich; Polevin S. D.; Rostov V. V. Vladislav Vladimirovich (Oral Session, 2008)
Title screen